Linking specification to differentiation: From proneural genes to the regulation of ciliogenesis - zur Lage, Petra I (Landes Bioscience, 2011)
Much of developmental biology is concerned with the processes by which cells become committed to particular fates in a regulated fashion, whereas cell biology addresses, among other things, the variety of differentiated forms and functions that cells can acquire. One open question is how the regulators of the former process lead to attainment of the latter. “High-level” regulators of cell fate specification include the proneural factors, which drive cells to commit as precursors in the sensory nervous system. Recent research has concentrated on the gene expression events downstream of proneural factor function. Here we summarize this research and describe our own research that has provided clear links between a proneural factor, atonal and the cell biological program of ciliogenesis, which is a central aspect of sensory neuron differentiation.